"We see a real opportunity around food waste": exploring the relationship between on-farm food waste and farm characteristics. Issue 8 (14th September 2018) - Janousek, Arlene; Markey, Sean; Roseland, Mark
ABSTRACT: The objectives of this research are to provide a better understanding regarding whether organic food producers produce more or less waste than nonorganic food producers, if food waste management practices differ between organic and conventional food producers, and what role producer food waste practices play in agricultural sustainability. This qualitative study found no conclusive differences between organic and nonorganic food producers regarding volume and management of on-farm food waste; however, different farm characteristics were found to intersect in numerous ways, resulting in a variety of impacts associated with on-farm food waste. Additionally, all research participants indicated that the factor most likely to encourage them to address on-farm food waste is cost savings. To fully address food waste, actions oriented toward minimizing and sustainably managing food waste must be undertaken in a collaborative manner across all stages of the food supply chain.